2009
DOI: 10.2135/cropsci2009.01.0018
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal Metabolism and Transport of Tall Fescue Ergot Alkaloids

Abstract: Circumstantial evidence suggests ergovaline is the putative toxin causing fescue toxicosis. However, several investigators suggest lysergic acid may be involved as well. Therefore, the purpose of this study was to (i) determine the metabolic fate of ergot alkaloids in ruminants, (ii) investigate gastric transport, and (iii) validate these findings in vivo. Ruminal metabolism of the alkaloids was determined by inoculating endophyte‐infected and endophyte‐free tall fescue [Lolium arundinaceum (Schreb.) Darbysh.]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 24 publications
3
44
0
Order By: Relevance
“…Total urinary EA concentration increased after 1 day of grazing, peaked on day 14, and remained elevated. The trend in urinary alkaloid excretion was consistent with previous studies (Ayers et al, 2009;Hill et al, 2000;Stuedemann et al, 1998), indicating animal's response to E+ grazing from this experiment is typical.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Total urinary EA concentration increased after 1 day of grazing, peaked on day 14, and remained elevated. The trend in urinary alkaloid excretion was consistent with previous studies (Ayers et al, 2009;Hill et al, 2000;Stuedemann et al, 1998), indicating animal's response to E+ grazing from this experiment is typical.…”
Section: Discussionsupporting
confidence: 91%
“…Rapid ergovaline metabolism and distribution to liver and kidney tissues also impedes its identification in the plasma (Ayers et al, 2009;De Lorme et al, 2007;Zbib et al, 2014). Besides using a broad, non-ergot alkaloid focused extraction method, some EA metabolites might not have been identified because of the lack of matching MS/MS spectra in existing reference metabolomics databases.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…If ergovaline is still being released as tissues turn over, then this will extend the time it takes for an animal to recover (as ergovaline is re-released) and clear ergovaline from their system. Alkaloid concentrations in ruminal fluid have been reported to decrease within 24 h of removal from endophyte-infected tall fescue pasture, and decrease to zero within 3 days after removal (Ayers et al 2009). Aiken et al (2011b) detected alkaloids (lysergyl) in urine collected from lambs still 4 days after switching them from an AR6 to an endophyte-free perennial ryegrass pasture, suggesting that the alkaloids are coming from a source other than rumen contents.…”
Section: Bioaccumulation and Excretion Of Ergovalinementioning
confidence: 99%
“…This is the first known report to show that ergovaline crosses the bovine rumen epithelium. Ayers et al (2009) showed that ergovaline did not cross bovine rumen epithelium isolated in a parabiotic chamber; however, the concentration used in their experiment may have resulted in serosal concentrations below the limit of detection. The estimation of flux rates presented here are significantly lower than those reported for ergotamine transport across ovine rumen and omasum tissue (Hill et al, 2001) as well as ergovaline movement across Caco-2 cells (Shappell and Smith, 2005).…”
mentioning
confidence: 91%